Diagnosing listening and reading skills in the Chinese EFL context: Performance stability and variability across modalities and performance levels. (June 2022) - He, Lianzhen; Xiong, Lidi; Min, Shangchao
Abstract: This study employed cognitive diagnostic modeling to examine whether learners' performance on the common subskills of listening and reading varied across modalities and performance levels, aiming to provide a better understanding of the similarities and differences between listening and reading in the Chinese EFL context. Specifically, we retrofitted a large-scale EFL test taken by 797 non-English-major undergraduates. We utilized the G-DINA package in R to obtain test takers' mastery patterns of global and local subskills in the listening and reading tests and further compared them through a mixed-design ANOVA. The results showed that the comprehension subskills were manifested similarly in listening and reading, but a modality effect did exist. Learners generally performed worse in listening and their mastery status of local and global skills was significantly different across modalities in that learners fulfilled global tasks better in listening and local tasks better in reading. The high-performing group mastered global skills better in listening and local skills better in reading while the low-performing group mastered global skills better in both listening and reading. The findings of the study provide backing for a modality effect in L2 comprehension, encouraging comprehension theorists and language teachers to reconsider the value of the modality-specific characteristics.